The Influence of Independence Curriculum Development on Mandarin Language Learning - Kariyati, Ani; Agustina; Yulia, Novia; Djoni (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
The fundamental thing about curriculum development is that there are deep changes and have quite a big impact on Mandarin language learning in educational institutions, especially schools that collaborate with countries that use second international languages for communication. As the world becomes more connected, the need for effective command of Mandarin is more important than ever. With curriculum development, educators can gain insight into innovative approaches to teaching and learning Mandarin. The problem faced by teachers of Mandarin as a foreign language is a lack of understanding of the curriculum in accordance with the demands of the times. Curriculum development greatly influences Mandarin learning. This will have an impact on the difficulty of achieving language mastery by students. A literature and reference search was conducted to address this issue. Here the author explores articles that examine and discuss the findings conceptually, the implications of the development of the Merdeka curriculum which has been influential in the formation of Mandarin language learning. Innovation and renewal are also a necessity for Chinese language learners. Apart from that, it will challenge Mandarin teachers to organize teaching materials within the concept of curriculum development that follows developments and demands of the times.